REVIVING SPORTS JOURNALISM FOSTERING YOUTH ENGAGEMENT AND ETHICAL REPORTING - Irshad Hassan C; Dinil S (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
This study examines the changing role of sports journalism in India, with a focus on Kerala, and its impact on youth participation and ethical reporting. Historically, sports journalism helped promote grassroots talent and athletes from rural areas, like Major Dhyan Chand and Dara Singh. However, the current media landscape has shifted towards celebrity-focused coverage, especially in cricket, leading to less attention on lesser-known sports and rural athletes. This change has contributed to a decline in youth participation in sports, particularly in Kerala, where sports culture has weakened. The study also highlights ethical issues in modern sports journalism, such as prioritizing appearance over athletic skill, which has led to exclusionary practices and a limited sports focus. The paper calls for reforms in sports journalism, including better education, journalist training, and changes in media practices to promote merit-based reporting and a more inclusive sports culture. Ethical sports journalism, it suggests, can help revive youth interest in sports and improve societal health and values.